Varta ag seizes opportunity in segment set to dominate the battery market - Magalhães, Manuel Maria Cabral de Menezes de Meireles e (2022)
This paper accesses VARTA AG as a potential PE House target. VARTAAG is a company present in some of the highest growing segments of the battery market–and has the technological and production capacity that allowing it to keep track with market growth. More over, VARTA has the technological capacity to tapinanun explored segment, by the company, of the battery market–the hight growth segment of the Electric Vehicle(EV) Batteries. This Investment Co capable of pursuing of interesting value creation strategies, EV Battery Facility and Materials Recycling facility, that make VARTA an interesting target fo ra Leveraged Buy Out(LBO).